Topical Mitomycin C Application in Pediatric Patients with Recurrent Esophageal Strictures—Report on Unfavorable Results - Madadi-Sanjani, Omid; Zimmer, Julia; Gosemann, Jan-Hendrik; Ure, Benno M.; Lacher, Martin; Boehm, Roland (European Journal of Pediatric Surgery, 2018)
Objective Recurrent esophageal strictures (ESs) following esophageal atresia repair or caustic ingestion represent a common clinical problem. Recently, Mitomycin C was reported to improve the outcome of patients by reducing the number of endoscopic dilatations. However, other groups failed to exhibit a beneficial effect. We report on our experience with topic Mitomycin C application following endoscopic dilatation for recurrent ES.Methods Retrospective chart review of patients with ES treated at the Hannover Medical School (Location A) and the University of Leipzig (Location B) between 2009 and 2015. A Mitomycin C-soaked cotton swab was endoscopically placed at the area of stricture in all subjects. Successful treatment was defined as resolution of stricture after Mitomycin C therapy with not more than three dilatations thereafter. Our results were compared with published outcomes of alternative studies that involved 10 or more patients.Results A total of 11 children received Mitomycin C concurrently with endoscopic dilatations. Seven children (64%) had gross type C esophageal atresia, two patients (18%) gross type A esophageal atresia, and two children (18%) caustic injury.After a median follow-up of 34 months (range, 14–75 months) and a median number of 3 ± 2.5 dilatations with Mitomycin C application per patient (range, 1–9), 6 of 11 patients (55%) achieved a resolution of their strictures. Five patients (45%) did not respond to Mitomycin C therapy, of which two needed esophageal redo-surgery.Conclusion We failed to confirm the high success rates of Mitomycin C treatment for recurrent ESs. Given the fact that there is limited data to prove the beneficial effect of Mitomycin C treatment, pediatric surgeons should carefully consider whether the advantages of this therapy outweigh the necessity of life-long endoscopic follow-ups. Further randomized controlled studies are recommended.
Keywords: mitomycin C; esophageal stricture; endoscopic balloon dilatation; esophageal atresia; caustic ingestion